Multi-Faction : Multi-Factor Authentication Using Object Detection, Graphical Password And Voice Authentication - Abu Zarim, Mohd Abu Hanif Qusyairi; Beh Mei Yin, Delina (Journal of Computing Technologies and Creative Content, 2016)
This Multi-Factor Authentication using Object Detection, Graphical Password and Voice Authentication is being developed for a few objectives and evaluate the functionality of the proposed system. Based on the previous system, they using common log in via username and password is predictable, and text-based password is difficult to memorise. Nowadays, people use all kinds of security system to make sure their property and data is secured such as using password and User ID for protection. Unfortunately, all these security system is not secured at all because the pin code can be hacked, the ID card can be stolen and duplicated. This system is user friendly, easy-to-understand and put the security of user in the first priority. The system is safe and trustable to store all the information from the user.